Health and Safety of Hyderabad Industries’ Labor. Causes and Awareness - Khoso, A. R.; Akhund, M. A.; Memon, A. H.; Siddiqui, F.; Khahro, S. H. (Engineering, Technology & Applied Science Research, 2017)
Labor’s health and safety (H&S) is a matter of concern for all industries. Occurrence of accidents in industries is becoming a common issue. Both white collar and blue-collar workers are not shielded from materials that damage their health. This study identifies the critical factors affecting labor’s H&S in Hyderabad, Pakistan industries. The awareness of labor regarding prevention and consequences that affect workers’ H&S is also a matter of interest of this research. The severity of factors was determined through questionnaire survey from experts, H&S supervisors and managerial staff of industries. For the descriptive analysis the software SPPS 24.0 was used. This research also includes interviews form industry laborers about awareness regarding H&S critical factors. The results show that, Improper PPE use, operating machines that are poorly maintained, long term exposure to high intensity noise, working extended and irregular hours and lack of knowledge of working instruments are the critical causes of accidents. Also 60.9%, 73.9%, 69.6%, 78.3% and 89% of workers are not aware about these causes and their consequences. Thus, this research is a road map for industrial employers, law makers, local, provisional and federal Government of Pakistan in order to help minimizing the workplace accidents and the providing of safe and secure working environment for laborers.